2005
DOI: 10.1002/jso.20228
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatment for gastric cancer: Approaches and selection process

Abstract: Minimally invasive treatment of gastric cancer has emerged as a result of the technical advances, better understanding of gastric physiology, and more knowledge of the biologic behavior of gastric cancer. This treatment results in improved quality of life embodied by smaller incisions, reduced length of hospital stay, and a faster return to productive life. However, minimally invasive treatment for gastric cancer must take into consideration the potential effects of these techniques on tumor dissemination at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 63 publications
0
32
0
5
Order By: Relevance
“…The prognosis is different between early and advanced gastric cancer. The average 5-year survival rate in patients with early gastric cancer is over 90%, and it is up to 94.2% in patients without lymph node metastasis (Noh et al, 2005). The incidence of lymph node metastasis in early gastric cancer range from 2.6% to 4.8% in mucosal cancers and 16.5% to 25% in submucosal cancer (Tsujitani et al, 1999;Kim et al, 2004;Roviello et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is different between early and advanced gastric cancer. The average 5-year survival rate in patients with early gastric cancer is over 90%, and it is up to 94.2% in patients without lymph node metastasis (Noh et al, 2005). The incidence of lymph node metastasis in early gastric cancer range from 2.6% to 4.8% in mucosal cancers and 16.5% to 25% in submucosal cancer (Tsujitani et al, 1999;Kim et al, 2004;Roviello et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because of possible residual tumor and lymph node metastasis in case of submucosal invasion, gastrectomy with lymph node dissection should be considered regardless of margin involvement status after EMR/ESD. Furthermore, because most of the metastasized lymph nodes in patients with submucosal invasion were confined to level 1 group [24], laparoscopic gastrectomy with D1 þ b dissection can be the choice of further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of lymph node metastasis in early gastric cancer results in a worse prognosis, as reported by Kitamura et al (1997) and Folli et al (2001). Noh et al (2005) reported that the 5-year survival rate of early gastric cancer without lymph node metastasis is 94.2% and that of early gastric cancer with lymph node metastasis is 87.3%. Nio et al (1993) reported a 5-year survival rate of 95% for N1 patients and 68.4% for N2 patients for early gastric cancers, and Miwa et al (1984) observed similar rates of 90% and 79%, respectively.…”
Section: Discussionmentioning
confidence: 99%